Determinación por medio de simulación los factores de fricción para el campo Guatiquía ubicado en la cuenca de los Llanos Orientales (2018)
The main objective of this project is to determine the friction factors for three wells that are planned to be drilled in the Guatiquía Field, where the operating company is Frontera Energy and Baker Hughes, a GE company, provides planning and drilling services. In the Guatiquía Field there is the Aventador_3 type well, which is the reference point for the analysis of the wells that will be simulated in this project. The analysis of the factors that affect a drilling process and how these are reflected in the torque readings that can trigger operational problems is presented; which in turn translate into increases in time and costs, is not allowed during the planning stage. This work is based on the drilling process of a type well (Aventador_3) and can be used as a guide for the correct practices and the factors that must be taken into account for the drilling of a well. in the Guatiquía Field.